Evaluation of peak expiratory flow rate with severity of lower respiratory tract infection in children of Hadoti region - Tripathi, Shobhit Kumar; Sahu, Yatendra; Meena, Neelam; Rathore, Anjali (International Journal of Contemporary Pediatrics, 2023)
Background: Correlation of peak expiratory flow rate (PEFR) with severity of lower respiratory tract infection (LRTI) and comparison of PEFR with same age, sex, height and nutritional status of children of age group 7 to 18 years. Methods: This is a case control study in children in the age group of 7 to 18 years of both sexes suffering from LRTI admitted in department of paediatrics of a tertiary care government hospital of Hadoti region. The duration of study was October 2019 to September 2020. Group 1 (case group) comprised of children having LRTI, whereas group 2 (control group) comprised of healthy and asymptomatic children There were 250 children in each group and they were further categorized into 3 age groups of 7-10 years, 11-13 years and 14-18 years. The PEFR of LRTI group children was compared with control group children with the similar age, sex as well as the anthropometric measurements. Results: In LRTI group, the PEFR had significant difference from control group, in all three age groups (p<0.0001). The study showed positive co-linear relationship between age, height, weight and BMI with PEFR in both males and females in LTRI and control groups. Conclusions: Effect of PEFR depends upon anthropometric measurements of children of different age group in both LRTI population and control population. In control group PEFR showed significant difference between boys and girls, but in LRTI group PEFR showed non-significant difference between boys and girl in their respective age groups.